Efektivitas Penerapan Video "Mengubah Sampah Plastik Menjadi Energi Berkelanjutan" di Kota Batam - Sandi Prasetyaningsih; Sherina Ayu Salsabilla (JURNAL INTEGRASI, 2022)
As the effect of cutting-edge technology, video can be used as educational media. Video education itself can be utilized for certain purposes; for example, to deliver information about the dangers of plastic waste in Batam. This study aims to analyze the video’s effectiveness that consists of the information about how to alter plastic waste into sustainable energy. A descriptive quantitative method has been applied in order to collect the data. It is about 150 respondents involved. Those respondents who are living in Batam. The result of this research is the video about how to change plastic waste into sustainable energy can deliver a concrete information. It also able to motivate the audience to be more aware about managing plastic waste. The video effect the audience to manage their plastic waste wisely. It can be seen for about 39% and 56, 22% of respondents highly agree and agree respectively about the effect of the video.